Influence of a Two-Stage Sintering Process on Characteristics of Porous Ceramics Produced with Sewage Sludge and Coal Ash as Low-Cost Raw Materials - Esam Al-Qadhi; Gaiye Li; Yaxing Ni (Advances in Materials Science and Engineering)
In this paper, the two-stage sintering process as a promising strategy has been adopted to prepare high-performance porous ceramics with high porosity. Sewage sludge and waste coal ash were used as raw materials and added were starch and CaCO3 as a mixed foaming agent. The chemical composition of the raw materials and mixed foaming agents were analyzed by standard techniques. All mixtures were prepared from fixed solid materials mixed at a ratio of 48 : 32 : 10 : 10 (wt.%) for coal ash, sludge, starch, and CaCO3, respectively, followed by granular molding, aging, sintering and property survey tests. The influence of heating rate, holding time, and heating temperature of the two stages on the characteristics of the as-obtained porous ceramics was deeply investigated. The properties investigated are apparent porosity, bulk density, compressive strength, and linear shrinkage. On the one hand, the results show that the major content of the raw materials is silica (SiO2). On the other hand, the results show that the first-stage sintering process had minimal influence on the properties, whereas the second-stage sintering process had a significant influence on the properties of the porous ceramics. With the optimized sintering parameters (temperature, heating rate, and holding time) of the first stage and second stage, we obtained a high-performance porous ceramic product with an apparent porosity up to 51.3%, bulk density up to 1.22 g/cm3, linear shrinkage up to 14.3%, and compressive strength up to 25.1 MPa. Also, the results of the phase composition and microstructure revolution showed sufficient glassy phases and feldspar (Ca, Na) (Si, Al)4O8, which are known to enhance bending strength of ceramics. A comparison of these properties and characteristics with those of standard porous ceramics revealed that the product developed in this study would compete favorably for real applications.